Potensi Wakaf Saham Sebagai Alternatif Wakaf Produktif Di Era Digitalisasi 4.5 - M. Asri Setiawan; Zaiful Anas (Al-Iqtisodiyah : Jurnal Ilmu Ekonomi dan Ekonomi Islam, 2025)
In the development of new waqf objects such as cash waqf, shares and securities emerged as a result of ijtihad ulama based on the motive of maximizing the benefits that would be felt by the recipient. Indonesia is a country with a Muslim majority population. Along with the increasingly widespread halal lifestyle, it also affects the investment style of the community with the emergence of the Islamic stock market and continues to grow. In Indonesia, the share waqf program will be launched by the relevant authorities. The purpose of this study is to find out the model for implementing share waqf in Indonesia later and to find out how to estimate the potential of share waqf in Indonesia. This study uses a qualitative approach and is categorized as a literature study using the metasynthetic method. The results show that there are two models of stock waqf management in Indonesia. Meanwhile, the potential of stock waqf is very large, in terms of the number of Muslims in Indonesia, the number of Islamic stock investors from year to year and the number of Islamic stock issuers on the Indonesian stock exchange. Abstrak Dalam perkembangan objek-objek wakaf baru seperti wakaf uang, saham dan surat berharga muncul sebagai hasil ijtihad ulama berdasarkan motif memaksimalkan manfaat yang akan dirasakan oleh penerimanya. Indonesia merupakan negara dengan penduduk mayoritas muslim. Seiring dengan kian maraknya gaya hidup halal, maka hal tersebut juga berpengaruh kepada gaya investasi masyarakat dengan munculnya bursa saham syariah dan terus berkembang. Di Indonesia sendiri akan di launching program wakaf saham oleh otoritas terkait. Tujuan dari penelitian ini adalah untuk mengetahui model penerapan wakaf saham di Indonesia nantinya serta untuk mengetahui bagaimana perkiraan potensi wakaf saham di Indonesia Penelitian ini menggunakan pendekatan kualitatif dan dikategorikan sebagai studi pustaka menggunakan metode metasintesis. Hasil menunjukkan bahwa terdapat dua model pengelolaan wakaf saham di Indonesia. Sedangkan potensi dari wakaf saham sangat besar, ditinjau dari jumlah umat Islam di Indonesia, jumlah investor saham syariah dari tahun ke tahun serta jumlah emiten saham syariah pada bursa efek indonesia.